2016
DOI: 10.1136/jech-2015-206827
|View full text |Cite
|
Sign up to set email alerts
|

Where do people live longer and shorter lives? An ecological study of old-age survival across 4404 small areas from 18 European countries

Abstract: Clear and persistent spatial inequalities in old-age survival exist, suggesting that European social unity is still to be accomplished. These inequalities could arise from a myriad of population health determinants (eg, poverty, unhealthy lifestyles), which merit further study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
22
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 41 publications
1
22
0
2
Order By: Relevance
“…In a previous study assessing spatial differentials in survival across Europe (Portugal inclusive) we found a nearly 2-fold difference between old-age survival rates in Portugal (Ribeiro et al, 2016). Within Porto differentials were even wider (2.5-to 2.8-fold difference), which is consistent with the literature on this topic.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…In a previous study assessing spatial differentials in survival across Europe (Portugal inclusive) we found a nearly 2-fold difference between old-age survival rates in Portugal (Ribeiro et al, 2016). Within Porto differentials were even wider (2.5-to 2.8-fold difference), which is consistent with the literature on this topic.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, we had to derive a measure of old-age survival ( = r i y n i i ) that expresses the probability of people aged 75-84 years surviving for an additional ten years, i.e., surpassing the average life expectancy (Ribeiro et al, 2016). Where r i is a ten-year survival rate, i ¼1,…,109 denotes area, the variable y represents the population aged 85-94 years old in 2011 and n the population aged 75-84 years old ten years before, in 2001.…”
Section: Outcomementioning
confidence: 99%
“…One ecological study in 18 European countries showed that urbanization of poverty and the rise in unhealthy lifestyles produced drastic effects on life expectancy of elderly adults, due to non-communicable chronic diseases [25].…”
Section: Discussionmentioning
confidence: 99%
“…One needs to wonder when the environment affects survival, as environmental effects might differ by age. Sardinia is, for example, known for its high share of centenarians (Poulain, Herm, & Pes, 2013), but is not known for its low mortality rates between ages 85 and 94 in comparison to other regions in Europe (Ribeiro et al, 2016). Studying whether longevity clustering increases or decreases over the life course helps to pinpoint which causes of mortality are suppressed, which in turn can give important insight into the mechanisms underlying geographic clustering of longevity.…”
Section: Introductionmentioning
confidence: 99%